Marco conceptual para la evaluación de programas de salud - Montero Rojas, Eiliana (Población y Salud en Mesoamérica, 2004)
<span style="color: #000000; font-family: 'Times New Roman'; font-size: medium; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; display: inline !important; float: none;">Evaluation, as a discipline, is an relatively new area of the Social Sciences, thus, its explicit incorporation in health programs and systems has appeared somehow late. This article presents elements of a conceptual framework to conceive and use the evaluation in health programs. Evaluation is defined as a tool for decision making, current tendencies and themes in the field are discussed, as well as key concepts such as program theory and needs assessment. Finally, a first approach to two key concepts in evaluation of health programs, quality and equity, is presented.